2007
DOI: 10.4049/jimmunol.179.10.6704
|View full text |Cite
|
Sign up to set email alerts
|

Strength of Stimulus and Clonal Competition Impact the Rate of Memory CD8 T Cell Differentiation

Abstract: The developmental pathways of long-lived memory CD8 T cells and the lineage relationship between memory T cell subsets remain controversial. Although some studies indicate the two major memory T cell subsets, central memory T (TCM) and effector memory T (TEM), are related lineages, others suggest that these subsets arise and are maintained independently of one another. In this study, we have investigated this issue and examined the differentiation of memory CD8 T cell subsets by tracking the lineage relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
125
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(144 citation statements)
references
References 53 publications
19
125
0
Order By: Relevance
“…Currently, it is not yet settled whether re-expression of CD62L in activated T cells occurs in vivo. In an adoptive transfer system using physiologically appropriate numbers of TCR transgenic T cells, conversion of effector memory T cells (T EM ) to central memory T cells (T CM ) cells by re-expression of CD62L was not observed (54), whereas in a recent paper CD62L reacquisition by a polyclonal population of antiviral effector CTLs was reported (55). Given this uncertainty, we favor the scenario that most FIV CD8 ϩ T cells probably give rise to the dominant, terminal FIII subpopulation.…”
Section: Discussionmentioning
confidence: 97%
“…Currently, it is not yet settled whether re-expression of CD62L in activated T cells occurs in vivo. In an adoptive transfer system using physiologically appropriate numbers of TCR transgenic T cells, conversion of effector memory T cells (T EM ) to central memory T cells (T CM ) cells by re-expression of CD62L was not observed (54), whereas in a recent paper CD62L reacquisition by a polyclonal population of antiviral effector CTLs was reported (55). Given this uncertainty, we favor the scenario that most FIV CD8 ϩ T cells probably give rise to the dominant, terminal FIII subpopulation.…”
Section: Discussionmentioning
confidence: 97%
“…After acute infections, the percentage of memory T cells with central memory phenotype increases steadily over time. Although the exact reasons for this observation are still a matter of debate (18,32,33), one possible explanation is the previously demonstrated capability of central memory T cells to undergo more rapid basal proliferation compared with effector memory T cells (18). Whether this accelerated proliferation is related to the lymph node environment or an intrinsic property of central memory T cells is unclear.…”
Section: Cd62lnc and Wt Cd8 T Cells Show Equal Proliferative Potentiamentioning
confidence: 99%
“…Following expansion, acutely activated T cell populations enter a phase of programmed contraction, during which the vast majority of antigen-specific shortlived effector T cells undergo apoptotic cell death. A small subset of memory precursor effector T cells survive contraction and eventually differentiate into memory T cells capable of long-term survival, even in the absence of antigenic stimulation [1][2][3][4][5][6]. We have previously found that a critical window of in vivo interaction exists between resting T cells and growing tumors, after which resting T cells are no longer capable of maximal proliferative expansion in response to antigenic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The size of a memory T cell population is a function of the clonal burst size of T cells present at the moment of maximal proliferative expansion and the rate of apoptotic contraction that takes place thereafter; by negatively impacting both of these variables, the suppressive influence of melanoma would be expected to markedly impair the generation of new T cell memory [3][4][5][6]. We previously observed significantly smaller numbers of LCMV-specific MPECs 10 days after viral infection; in the present analysis, we confirmed that there are markedly smaller numbers of LCMV-specific memory T cells present 26 days after viral infection [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation